Motion tracking of a wind turbine blade during lifting using RTK-GPS/INS. (1st October 2018) - Maes, K.; De Roeck, G.; Lombaert, G.
Highlights: A case study of object motion tracking is presented. The motion of a turbine blade during a hoisting operation is measured using RTK-GPS/INS. Reference data are obtained from three Leica total stations. Special focus goes to fusion of data obtained from different measurement systems. Abstract: This paper presents a case of object motion tracking where a real-time kinematic Global Positioning System (RTK-GPS) is used for correction of data obtained from an inertial navigation system (INS). The displacements obtained from the RTK-GPS and the accelerations obtained from the INS are combined using an unscented Kalman filter (UKF). The combined data are used to assess the motion of a 6 MW turbine blade during a hoisting operation and are compared to the blade motion obtained by use of three Leica total stations, that have been used for verification. Special focus in this paper goes to merging of heterogeneous data (displacements, rotations, and accelerations) obtained from different measurement systems. Analysis of the motion data shows that the RTK-GPS/INS measurement system allows for very accurate recording of displacement and rotation measurements.